2019
DOI: 10.1111/ajpy.12231
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence research in Australia: Past contributions and future directions

Abstract: Emotional intelligence (EI) is an intriguing and popular area of research, focusing as it does on individual differences in qualities at the intersection of intelligence and emotion. Research to date has focused on three key questions: (a) How to define EI? (b) How to measure EI? and (c) What is EI good for? This review describes the key contributions of Australian researchers to these questions before outlining the current focus and future directions of EI research in Australia. Australian research teams have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
0
18
0
2
Order By: Relevance
“…Different measures of EI abilitiesability tests vs. self-reportsshow to converge only mildly, suggesting that they measure different constructs (ability vs. trait EI; Buchich & MacCann, 2019). A main disadvantage of self-reports as measures of own abilities is especially obvious in studies of children and adolescents because the development of their abilities has mostly not finished yet and thus they could have less insight into own abilities compared to adults (Billings at al., 2014).…”
Section: Measuring Ei In Younger Age Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different measures of EI abilitiesability tests vs. self-reportsshow to converge only mildly, suggesting that they measure different constructs (ability vs. trait EI; Buchich & MacCann, 2019). A main disadvantage of self-reports as measures of own abilities is especially obvious in studies of children and adolescents because the development of their abilities has mostly not finished yet and thus they could have less insight into own abilities compared to adults (Billings at al., 2014).…”
Section: Measuring Ei In Younger Age Groupsmentioning
confidence: 99%
“…Having in mind the findings from different factor-analytic studies conducted under Mayer and Salovey's model, our study included the measures of the first (perception of emotions), third (understanding emotions), and fourth level (managing own and others emotions) abilities of their model (Buchich & MacCann, 2019;Fan, Jackson, Yang, Tang, & Zhang, 2010;Mayer et al, 2016;Roberts et al, 2006).…”
Section: Aims Of This Studymentioning
confidence: 99%
“…Ample evidence for the high international impact of Australian personality research can also be found in Bucich and MacCann's (, this issue) review of Australian researchers' contribution to the study and assessment of emotional intelligence. Although that contribution is not as widely recognised as it might be, Bucich and MacCann demonstrate that local and expatriate Australians have had a disproportionate presence at the leading edge of emotional intelligence research and its application.…”
mentioning
confidence: 90%
“…As discussed previously, the various models are widely discrepant, and the correlation between models is so narrow that concerns have been raised as to whether the tests are measuring the same construct (Bucich & MacCann, 2019;Hughes & Evans, 2018;McCleskey, 2014;Mestre et al, 2016). Debate on the psychometric properties of each test and whether the factors measure what they intend to continues in the organisational behaviour and psychology literature (Conte, 2005;Fiori & Vesely-Maillefer, 2018;Hughes & Evans, 2018;Matthews, Roberts, & Zeidner, 2004;McCleskey, 2014;Mestre et al, 2016).…”
Section: Emotional Intelligence: Conceptualisationmentioning
confidence: 99%
“…There is continuing scholarly debate over the definition and measurement of emotional intelligence (Bucich & MacCann, 2019;Hughes & Evans, 2018;Maccann, Joseph, Newman, & Roberts, 2014;McCleskey, 2014), and this controversy will be discussed with reference to the various models and measures available.…”
Section: Introduction To Emotional Intelligence -Early Theoretical Dementioning
confidence: 99%